PELATIHAN ANALISA STRATEGI MANAJEMEN “BAGI BUMDES DESA WISATA TUGU SELATAN” - Hamizar, Hamizar; Purwitasari, Maria Evy; Lutviani, Metya; Subagiyo, Subagiyo; Oktaviani, Featy; Syamsurizal, Syamsurizal (JURNAL ABDIMAS PLJ, 2025)
Village-Owned Enterprises, hereinafter referred to as BUMDes, are a village economic institution/entity that is a legal entity formed and owned by the Village Government, managed independently and professionally with capital that is wholly or mostly separated village assets. Ultimately, BUMDes was formed with the aim of increasing business opportunities in order to strengthen village autonomy and reduce unemployment. With Law No. 6 of 2014, the village government is given broader authority in terms of developing and empowering the economy of the village community in accordance with the potential, opportunities and capabilities of the village. However, many economic potentials of villages cannot be optimally utilized by the village to improve the economy and welfare of the community due to limited management strategies in managing BUMDes businesses and limited Human Resource capabilities in managing BUMDes. To achieve this goal, the Lecturers together with Students of the LP3I Jakarta Polytechnic held incidental training for the community and BUMDes Managers of Tugu Selatan Tourism Village in order to provide knowledge and understanding of SWOT analysis and Management Strategy so that it is hoped that the community and BUMDes Managers can further optimize the efforts that are currently being carried out and analyze how to make Tugu Selatan Tourism Village more advanced and developed and known by the wider community.